IMPLEMENTASI BUKU PILAR SEBAGAI UPAYA PENGUATAN KARAKTER - Fadwa Salma Syarafa; Fadlullah; Kristiana Maryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the importance of character strengthening in early childhood as the foundation for shaping children’s personality and positive behavior. One of the efforts carried out by educational institutions is through the implementation of pillar books containing character values integrated into daily learning activities. This study aimed to describe the implementation of pillar books as an effort to strengthen the character of childern aged 5-6 years at RA Al-Izzah and to indentify the supporting and inhibiting factors in its implementation. This research used a qualitative approach with a descriptive method. The research subjects consisted of the principal, classroom teachers, and children aged 5-6 years at RA Al-Izzah. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used data reduction, data presentation, and conclusion drawing. The validity of the data was obtained through source and technique triangulation. Based on the results of the study, the implementation of pilar books at RA Al-Izzah has been carried out well and has been able to become an effective effort to strengthen early childhood character through habituation and role modeling in daily activities.